Capitalism and private nature reserves: the taming of Mala Mala land claim - Ghedi Alasow, Khadra (Department of Environmental and Geographical Science, 2021)
Capitalism has evolved globally by disciplining its key features to suit new markets and changing socio- economic environments. These features include private property, labour and neoliberalism. Whilst capitalism has managed to become a well-established system, occasionally it is confronted with challenges which expose its callous nature. In South Africa, land restitution calls into question capitalism's operation as it disrupts the conventional process of profit accumulation. This is evident when looking at the manner in which land claims are settled in private nature reserves that are under a land claim. Private nature reserves have been structured to bring together capitalism's key features of property, labour and neoliberalism and therefore become interesting sites on which to study how they react to land restitution. This study uses Mala Mala Game Reserve to investigate how capitalism unfolds in the game reserve. It specifically looks at the conservation business, labour conditions, and the settlement of the land claim in the reserve. It begins by analysing the structuring of the conservation business to fit capitalism's objective of profit accumulation. The emphasis here is on the relationship between capitalism and nature, and how the conservation business is built on the commodification of nature. It traces the business foundation of Mala Mala over time to understand how the reserve became a luxurious safari destination that target a small, select group of wealthy, mainly international tourists. The reserve promises quality wildlife viewing and luxury accommodation for its guests, which it is able to offer through the commercialisation of nature in a manner that is often viewed as ethical to the greater public, yet a closer look at the operation of the reserve shows the unaccounted cost of exclusion, dispossession and exploitation. These impacts are further contextualised in the second part of the study, which documents the structuring of labour as a condition for building the reserve's economic success. Labour is an important necessity for capitalism's operations and its conditions show us the fierce manner in which surplus value is extracted. The creation of the cheap labour system in South Africa played an important role in building conservation areas. The success of conservation business in private nature reserves routinely depends on conservation labour. The study finds that cheap labour in Mala Mala is secured through the adoption of a migrant labour system. Such a system highlights the social ‘cost' (labour) of capital accumulation that takes place in the reserve. While the first two parts of the study explain how capitalism has shaped the conservation business in Mala Mala, the last section investigates what happens when this almost perfectly structured system is challenged through land claims. The study finds that the clash between conservation business and land restitution produce a model of land reform that chime with neoliberalism. Backed by government and landowners, the model separates business ownership from landownership in order to guarantee capital accumulation. This study contributes to our understanding of land restitution in private nature reserves in South Africa and the land restitution model it produces.